The Meaning of Giving Food Souvenirs: From the Perspective of Generation Z Immigrants in Yogyakarta City - Kusumaningrum, Haritsah; Kusumawati, Pipin; Tyas, Dyah Wahyuning; Fitriana, Fitriana (Journal of Indonesian Tourism, Hospitality and Recreation, 2024)
ABSTRACTYogyakarta city's rich cultural history, historical significance, and developing tourism sector have led to a substantial demand for food souvenirs. This study aimed to assess the importance of food souvenirs obtained by Generation Z migrants in Yogyakarta City. The study conducted a quantitative descriptive analysis. The sample comprised 100 respondents who were Generation Z citizens, held non-DIY ID cards, and had personally purchased food souvenirs from Yogyakarta for giving to their family or friends in their homeland. This research employs dependent variables defined by the provided variables, while the independent components comprise emotional variables and cultural habits. The statistical analysis was employed to determine the extent to which the significance of a food souvenir motivates an individual's act of gifting. Multiple linear regression was used in the study, along with tests to look for deviations from common assumptions, including heteroscedasticity, multicollinearity, and autocorrelation. The research findings indicated that respondents had persisted in the tradition of giving food souvenirs to their families or loved ones. This illustrated that Generation Z has continued to maintain the tradition of presenting food souvenirs, reflecting the morals and traditions of Eastern culture.ABSTRAKYogyakarta selain terkenal sebagai kota pendidikan, juga merupakan kota budaya, kota perjuangan, dan kota pariwisata yang berdampak pada permintaan akan oleh-oleh makanan yang sangat besar. Penelitian ini bertujuan untuk mengetahui makna oleh-oleh makanan yang dibeli para penduduk generasi Z (lahir pada 1997–2012) pendatang di Kota Yogyakarta. Jenis penelitian ini adalah deskriptif kuantitatif. Responden penelitian berjumlah 100 orang yang merupakan penduduk generasi Z di DIY yang memiliki KTP non-DIY dan pernah membeli oleh-oleh makanan dari Yogyakarta secara langsung (bukan melalui e-commerce/marketplace) untuk diberikan kepada keluarga/teman di tempat asalnya. Intrumen penelitian digunakan variabel memberi sebagai variabel dependen, sedangkan variabel emosional dan variabel budaya sebagai variabel independen. Analisis statistik dilakukan untuk mengetahui seberapa besar makna oleh-oleh makanan menjadi dasar seseorang memberikannya. Metode yang digunakan adalah regresi linear berganda didukung dengan pengujian penyimpangan asumsi klasik, yaitu heteroscedasticity test, multicollinearity test, dan autocorrelation test. Hasil penelitian diketahui bahwa responden masih menganut dan menerapkan budaya memberi oleh-oleh kepada keluarga atau seseorang yang spesial bagi mereka. Membuktikan bahwa generasi Z masih memegang teguh budaya memberi oleh-oleh makanan karena hal tersebut adalah cerminan budaya timur dan nilai-nilai kebaikan tersebut diajarkan juga dalam keluarganya.